Perbandingan Aktivitas Antibakteri Ekstrak Etil Asetat Daun Rasamala (Altingia excelsa noronha) dan Bahan Pengisi 3 Mix terhadap Enterococcus faecalis - Risyandi Anwar; Suaeni Kurnia Wirda; Etny Dyah Harniati (Universitas Muhammadiyah Semarang, 2021)
Introduction : Lesion Sterilization and Tissue Repair (LSTR-3MIX) are new paradigm in caries care with or without involving pulp and periapical by using combination of three antibiotics. Bacteria that cause endodontic or root canal infection are dominated by Enterococcus faecalis, which is facultative anaerobic gram-positive bacteria and the bacteria are resistant against antimicrobial substance and often found in failed endodontic treatment. LSTR method is an effort that disinfects pulp lesions by killing the bacteria through using three antibiotics, which are metronidazole, ciprofloxacin, and minocyline. The use of several kinds of antibiotics can trigger the resistance of bacteria. However, it is needed an alternative of new antibiotic finding by using natural antibacterial herbal medicine as filler substance for endodontic that has antibacterial ability as balanced as 3MIX antibiotic pasta. Purpose : This research aimed at knowing the difference of antibacterial effect between rasamala leaf extract against E. faecalis bacteria that was compared with 3MIX antibiotic pasta. Method : The method used in this research was laboratory experiment by utilizing post test only control group design. This research was consisted of 6 treatment groups of rasamala leaf extract with concentration of 20%, 10%, 5%, 2,5%, 1,25%, and 1 control group of 3MIX antibiotic pasta. Result : 3MIX antibiotic was more effective in inhibiting the growth of bacteria rather than rasamala leaf extract in inhibiting the growth of Enterococcus faecalis. Conclusion : ethyl acetate from rasamala leaf extract was not more effective than 3MIX antibiotic in inhibiting the growth of Enterococcus faecalis.